Effect of (50%Isopropanol – 30%Methanol – 17%Xylene) Mixture on Corrosion Behavior of Pure Al and its Alloys in Simulated Fuel - Rana A. Majed; Majid H. Abdulmajeed; Slafa I. Ibrahem; Saja A. Abdul Maged; Zahraa S. Al-Saffar (Engineering and Technology Journal, 2014)
This work involves studying the effect of adding (50%Isopropanol – 30%Methanol – 17%Xylene) mixture on corrosion behavior of pure Al and its alloys in simulated fuel at room temperature. The results of electrochemical measurements indicate that the addition of this mixture lead to decreasing in corrosion rate values for pure Al and its alloys. Electrochemical measurements were carried out by potentiostat at weep rate of 3 mV/sec to estimate the corrosion parameters using Tafel extrapolation method, in addition to cyclic polarization test to know the pitting susceptibility of materials in tested medium. Generally, the cathodic Tafel slope (bc) were increased after adding mixture. But the anodic Tafel slopes (ba) were decreased except for Al-Cu alloy. The small anodic slope indicates the presence of a film on the surface of the tested material, which is less permeable and can even obstruct the metal dissolution reaction but still permits an electrochemical reaction to occur. This behavior can be achieved by the electronic density on oxygen atoms in alcohols.